Św. Kutbert - asceta, biskup i święty Kościoła anglosaskiego - Bulas, Ryszarda (Vox Patrum, 2006)
The author presents one of the best-known figures of northumbrian Church, in time of the transitional period from paganism to Christianity. On the base of two Lives of St. Cuthbert (The Anonymous life, Bede’s prose life) author describe life of Saint (childhood, youth, a monk, solitary life, a prior of Melrose and Lindisfarne, bishop of Northumbria). Finely author describes the spread of the cult of St. Cuthbert in Ireland, Scotland, North of England and Continent.